Analisis Hasil Belajar Siswa pada Pembelajaran PKn Materi Hak dan Kewajiban Kelas V SD Negeri 35 Palembang - Hamzah, Hamzah; Sukardi, Sukardi; Surmilasari, Nora (ANTHOR: Education and Learning Journal, 2022)
This study aims to determine student learning outcomes in PKn learning material rights and obligations for class V at SD Negeri 35 Palembang. This study uses a qualitative descriptive research method. Data collection techniques in this study are observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The results of the study show that the learning outcomes of PKn learning materials on the rights and obligations of class V students are in a low category. Judging from the value of learning outcomes in PKN learning the rights and obligations material in the table shows that student learning outcomes are at the student average score of 50 which is included in the less or still low category. In the indicator of Knowing the rights, obligations, and responsibilities as citizens 53% have not been able to answer the difference between rights and obligations. While on the indicator of Distinguishing rights, obligations, and responsibilities as citizens of the community 60% have not been able to distinguish between rights and obligations that must be accepted and they are carried out. teacher's efforts to improve student learning outcomes through the latest learning models and methods, good interaction, and communication between students and teacher.